ICT and Student Learning during Covid-19: Some Experiences of English as Second Language Learners - Khatoon, Humairah; Nadeem, Syedah Fawzia (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2026)
The outbreak of COVID-19 had a tremendous impact on almost all facets of schooling and caused substantial disruptions. Education was transferred entirely to the global shift towards online education due to the COVID-19 pandemic, and e-learning emerged as the most viable solution for the continuity of education, particularly in the context of K-12 schooling. This study is designed to investigate the experiences of English as a Second Language (ESL) students during the lockdown period. The primary goal of this research is to assess the students' novel encounters with online education and gauge the viability of virtual learning approaches. This will be accomplished by analysing the feedback and responses provided by 50 learners at the senior secondary level. The method of data collection is based on the questionnaire for students. Through data collection, the analysis will be done on the problems faced related to technical, academic, and communication challenges, and how they impacted online learning. This study on ESL education during the COVID-19 pandemic aims to determine whether ESL students found online learning satisfactory and whether they were able to meet the expected language learning performance standards. The study's outcomes will reveal the level of satisfaction and progress achieved by ESL learners in the context of online education.